KEBIJAKAN UNDP (UNITED NATIONS DEVELOPMENT PROGRAMME) DALAM MELIBATKAN DUTA INTERNASIONAL UNTUK PENCAPAIAN MILLENIUM DEVELOPMENT GOALS (MDGs) - , Fahrul Rozi, Drs. Samsu Rizal Pangabean, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Political constellation in the era of globalization was not dominated by formal actors (government actors), but international organizations also. The existence of international organizations is not only the complementary (complementary), but it has to be an actor who has an important role in resolving the problems that occur in the various countries of the world. And United Nations Development Programme (UNDP) is one of them. The existence of UNDP has a primary function as a UN organization that is involved in the development countries of the world. In 2001, UNDP and the supporting entity issuing achievement of the Millennium Development Programmes (MDGs). This program is a planned strategy to be implemented in the countries of the world from the year 2000 to 2015. MDGs is contains about eight provisions that is ratified in September 2000 at the United Nations Secretariat in New York United States. Achievement of the MDGs was faced with technical and non-technical problems. And the biggest obstacles is faced by UNDP are related to MDGs concept of universal while every country or region have many different problems to face. To fix those problems, one of the strategies adopted by the UNDP is to involve non-structural international ambassador. The existence of an international ambassador for the non-structural UNDP was able to support UNDP performances in achieving the MDGs. This research will be presented in detail about background, motivation, and also involvement of UNDP international ambassador to achieve the MDGs in many countries of the world.